Comparative evaluation of Integrated Solar combined cycle plant with cascade thermal storage system for different heat transfer fluids. (15th June 2022) - Khandelwal, Neelam; Sharma, Meeta; Singh, Onkar; Shukla, Anoop Kumar
Abstract: The existing conventional combined cycle power plant(s) are generally not getting the schedules for supply of power because of the high price of Natural Gas and are forced to remain idle or to run on part load. On the other side, the focus is on the capacity addition of power generation units based on the alternate sources mainly solar to counter the ill effects on environment through fossils fuel-based plant(s). In such a scenario, the combined cycle power plant(s) with its integration with solar (ISCC) can pave the way forward to provide an optimal solution to tap most of the power generation through solar power and to ensure grid stability through utilising the installed combined cycle power plant(s) at part or full load. It will be a win-win situation for solar plants as well as combined cycle power plants. This study presents an integration of Linear Fresnel collector solar system and latent heat cascade storage system with a 328.10 MW combined cycle power plant of north India for operating it as integrated solar combined cycle (ISCC). The present work discusses the configurations of integration of solar power generation cycle with the combined cycle power generation and presents the analysis of the performance of these integration configurations including the operation of gas turbine(s) at full load or part load. A MATLAB code is used for simulation to analyse the performance of ISCC by varying direct normal irradiation at different part-load condition of gas turbine with different heat transfer fluids such as water and molten salt, then also compare the performance of latent heat cascade thermal storage system with oil & molten salt as HTF. The effect of cascade thermal storage has also been analysed on the plant performance. The efficiency of ISCC with molten salt as HTF is 50.87% which is more than with water as HTF by 1.51%. The present study also brings out the saving of the fuel to figure out the financial benefit. However, the financial model has not been developed in the present work due to the dynamics of the price of natural gas internationally. The study also presents the analysis of the enhanced fuel-saving ratio and reduced emissions. Highlights: Linear Fresnel collector solar system with latent heat cascade storage is integrated to combined cycle power plant. Mathematical modelling of solar field, gas based combined cycle, latent heat cascade thermal storage. Analysis of the performance of the proposed system with MATLAB as simulation tool. Analysis of options to utilize the idle capacity of combined cycle power plants. Analysis the effect of integration of solar system in terms of saving of the amount of natural gas.